Evaluation of Antipsychotic Activity of Ethanolic Bark Extract of Myrica esculenta in Rats - Sapkota, Biswash; Acharya, Ankit; Dangi, Bishal; HV, Annegowda (Pharmaceutical Sciences and Research, 2020)
The antipsychotic properties of Myrica esculenta stem bark were evaluated. The stem bark was collected, shade dried, and pulverized. Extraction was carried out with 70% ethanol by occasional shaking. Preliminary phytochemical screening of the extract was investigated in this study. Antipsychotic activity was evaluated against apomorphine-induced stereotypy using cook’s pole climbing apparatus and haloperidol-induced catalepsy models. Bioamine determination of noradrenaline and dopamine was also performed. The extract contains phytochemicals, including glycosides, flavonoids, volatile oils, proteins, saponins, phenolics, and tannins. The result showed decreased apomorphine-induced stereotyped behavior. This study reported significant dose-dependent potentiation of haloperidol-induced catalepsy in rats and a longer time needed by the rat to climb the pole in a dose-dependent manner. Also, it significantly decreased brain dopamine and noradrenaline level. The ethanolic extract of M. esculenta exhibited significant antipsychotic activity in rats. Further neurochemical investigation is needed to explore the plant drug’s mechanism of action regarding anti-dopaminergic functions and establish the plant as an antipsychotic agent.